Engineering Design Process: A Review and Bibliometric Analysis - Sudrajat, Ujang; Ardianto, Didit; Permana, Irvan (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
Currently, science and technology is developing very quickly, so efforts are needed to balance this acceleration, especially in the world of education. Innovations in learning must always be done to keep pace with the development of science and technology. engineering design process (EDP) is one of the strategies available to implement STEM education, has been utilized by many STEM-related subjects educators as a mean to implement STEM (Hafiz and Ayop 2019). The engineering design process allows students to use mathematics and science inquiry to create and conduct experiments for potential design solutions.. The purpose of this paper is providing an extensive bibliometric literature review on engineering design process'. Articles obtained from the Google Scholar database using Publishing or Perish (PoP) software. There were 762 out of 999 articles found from Google Scholar data base ranging from 2016 to 2021 analyzed in this study. The chosen references were then managed using a referencing manager software namely Mendeley. In this research, VOSviewer software is used to classify and visualize the database that has been managed. Overall, this review provides an appropriate reference point for further research on engineering design process